Problems affecting the capitalist system and future threats to its stability (Economic and Political Thought, 2015)
The author argues that the economic condition of our societies has tobe viewed over a very long historical scale. The assumption made by FrancisFukuyama that history had somehow come to an end with the collapse ofthe former Soviet empire has proved to be an illusion. Fukuyama was thereimplying that the system of neoliberal economics had proved itself to bethe key to human happiness and welfare, and that once in place, nothingcould equal it. But after a quarter of a century, the doctrines of free marketeconomics are coming under increasing criticism. In many countries in whichthe principles have been applied, not only the traditional working classes arefeeling the pain as unemployment has risen, and incomes have remainedstatic even for those in work. The middle classes are also complaining aboutreduced expectations of prosperity, in the sense of static or even fallingincomes. It is obvious that younger generations are entering the workplacewith heavy debts from the cost of university education, and rises in theproperty market are putting the ambition of home ownership beyond theirreach. But all this has to be considered in the hard light of history. Whyshould capitalism, which has hardly existed for five centuries, be consideredthe default system for all future time, when the trail of collapsed civilisationsgoes back to the dawn of human existence on earth? But the wrangles ofeconomists and politicians may be set at naught by forces that may be entirelyoutside their control. Climate change may cause enormous damage even inthe present century. Linked with that is the question of mass migration, theconsequences of which are now plain to see. And scientists may experimentwith artificial intelligence at their peril. Once machines acquire the abilityto modify themselves, all may be over for capitalism – and the human race.